Hubungan Pengetahuan Ibu tentang Pentingnya 1000 Hari Pertama Kehidupan dengan Tumbuh Kembang Anak - Angelica, Valerie; Stella, Sancka; Solehudin, Solehudin (Journal of Nursing Education and Practice, 2024)
Introduction: Insight into the mother's knowledge of the importance of the first 1000 days of life and child growth and development is very important because child development is related to maternal stimulation. In preliminary studies, it was found that most children experienced delays in motor, cognitive, language, and socio-emotional. If the mother's knowledge of the first 1000 days of life is lacking, it will cause the growth and development of the child to be less than optimal. Objectives: To find out the relationship between the mother's knowledge about the importance of the first 1000 days of life with the child's growth and development. Method: Analytical research of correlation with cross sectional correlation approach.  A sample of 50 respondents from a total population of 100 respondents was taken by purposive sampling technique. This research instrument uses questionnaire sheets. This study used the Spearmen Rank correlation statistical test. Result: The results of the mother's knowledge of the importance of the first 1000 days of life with child growth and development obtained a value of Sig-value = 0.351. This means according to the Spearmen Rank test if the value of Sig-value = >0.050 then this study proved that there is no relationship between maternal knowledge about the importance of the first 1000 days of life with child growth and development. Conclusion: There is no relationship between the mother's knowledge about the importance of the first 1000 days of life and the child's growth and development.